2008
DOI: 10.1111/j.1460-9592.2008.02592.x
|View full text |Cite
|
Sign up to set email alerts
|

Single injection paravertebral block for renal surgery in children

Abstract: Single injection PVB provided clinically relevant postoperative analgesia in children undergoing major renal surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
24
1
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(28 citation statements)
references
References 25 publications
2
24
1
1
Order By: Relevance
“…The use of ultrasound guidance has led to new approaches to plexus anaesthesia in children (Fleischmann et Continuous paravertebral extrapleural infusions provided effective analgesia in infants following thoracotomy (Fisher et al, 1999 Level IV). Single-shot paravertebral injection provided effective analgesia after renal surgery (Berta et al, 2008 Level IV) and inguinal hernia repair Level IV).…”
Section: Chapter 10mentioning
confidence: 99%
“…The use of ultrasound guidance has led to new approaches to plexus anaesthesia in children (Fleischmann et Continuous paravertebral extrapleural infusions provided effective analgesia in infants following thoracotomy (Fisher et al, 1999 Level IV). Single-shot paravertebral injection provided effective analgesia after renal surgery (Berta et al, 2008 Level IV) and inguinal hernia repair Level IV).…”
Section: Chapter 10mentioning
confidence: 99%
“…In another study in paediatric patients undergoing renal surgery, the analgesic effects of a single TPVB injection were sustained for a mean of 600 min without additional analgesics, thus indicating the effective analgesic action of TPVB even without continuous administration. 15 TPVB in children has also been used quite successfully for outpatient anaesthesia. 16 Since its first description in 1994, the procedure of real-time ultrasound-guided regional anaesthesia has been widely used.…”
Section: Discussionmentioning
confidence: 99%
“…Berta et al [7] studied the effect of PVB on postoperative pain in children undergoing renal surgeries under general anaesthesia and reported that the median duration of postoperative analgesia was 600 min (range 180-720 min) and 10 patients (41.7%) did not need analgesia while 14 patients (58.3%) needed analgesia during the first 12 postoperative hours, but in our study the duration of postoperative analgesia was 16.25 ± 1.66 h (mean ± sd) and 7 patients (17.9%) needed analgesia during the first 24 postoperative hours. The differences between our results and Berta' s results may be due to different type of surgeries in both studies also in our study we used local anaesthetic drug pluse dexmetomidine which is known to potentiate the effect of local anaesthetics as reported by Esmaoglu A et al [20].…”
Section: Discussionmentioning
confidence: 99%
“…Both caudal and paravertebral blocks were used successfully in pediatrics to improve postoperative analgesia [6,7].…”
Section: Introductionmentioning
confidence: 99%